Analisis Kinerja Sumber Daya Manusia di SMP Negeri 1 Kamang - Misrawita; Zulfani Sesmiarni (STID Raudlatul Iman Sumenep, 2026)
This study aims to evaluate the performance of human resources (HR) in Islamic education at SMP Negeri 1 Kamang Magek through the Balanced Scorecard (BSC) approach. This research was conducted to answer the need for a comprehensive and contextual performance evaluation model, especially in the Islamic educational environment, which assesses not only professional aspects but also spiritual values such as trust and honesty. This study expands the evaluative approach by integrating nine key indicators, including Islamic values, as differentiators from previous research. This study uses a descriptive quantitative approach. Data was collected through an online survey using Google Forms that was distributed to 22 respondents, consisting of teachers and education staff. The instrument was developed from the Balanced Scorecard indicator and Islamic values, which consists of 35 closed-end statements divided into nine main indicators. Data analysis is carried out descriptively by calculating average scores to determine the classification of human resource performance. The results showed that most human resources were in the category of 'developing as expected', with the highest scores on indicators of professionalism (average = 4.45) and Islamic values (average = 4.41). The initiative and competency indicators received the lowest scores, 3.78 and 3.84, respectively. These findings emphasize the importance of continuous training to improve motivation, creativity, and technical competence. The limitations of this study include the small sample size of a single educational institution and the lack of in-depth construction validity testing. The practical implications of this study show the need for simultaneous strategies to improve human resources based on spirituality and professionalism. This research makes an original contribution by systematically integrating the BSC approach with Islamic values and can be a model for evaluating the performance of human resources in other Islamic educational institutions. Penelitian ini bertujuan untuk mengevaluasi kinerja sumber daya manusia (SDM) dalam pendidikan Islam di SMP Negeri 1 Kamang Magek melalui pendekatan Balanced Scorecard (BSC). Penelitian ini dilakukan untuk menjawab kebutuhan akan model evaluasi kinerja yang komprehensif dan kontekstual, khususnya di lingkungan pendidikan Islam, yang menilai tidak hanya aspek profesional tetapi juga nilai-nilai spiritual seperti kepercayaan dan kejujuran. Studi ini memperluas pendekatan evaluatif dengan mengintegrasikan sembilan indikator utama, termasuk nilai-nilai Islam, sebagai pembeda dari penelitian sebelumnya. Penelitian ini menggunakan pendekatan kuantitatif deskriptif. Data dikumpulkan melalui survei online menggunakan Google Formulir yang didistribusikan kepada 22 responden, yang terdiri dari guru dan tenaga kependidikan. Instrumen ini dikembangkan dari indikator Balanced Scorecard dan nilai-nilai Islam, yang terdiri dari 35 pernyataan tertutup yang dibagi menjadi sembilan indikator utama. Analisis data dilakukan secara deskriptif dengan menghitung nilai rata-rata untuk menentukan klasifikasi kinerja sumber daya manusia. Hasil penelitian menunjukkan bahwa sebagian besar sumber daya manusia berada dalam kategori 'berkembang seperti yang diharapkan', dengan skor tertinggi pada indikator profesionalisme (rata-rata = 4,45) dan nilai-nilai Islam (rata-rata = 4,41). Indikator inisiatif dan kompetensi mendapatkan skor terendah, masing-masing 3,78 dan 3,84. Temuan ini menekankan pentingnya pelatihan berkelanjutan untuk meningkatkan motivasi, kreativitas, dan kompetensi teknis. Keterbatasan penelitian ini termasuk ukuran sampel yang kecil dari satu lembaga pendidikan dan kurangnya pengujian validitas konstruksi yang mendalam. Implikasi praktis dari penelitian ini menunjukkan perlunya strategi simultan untuk meningkatkan sumber daya manusia berbasis spiritualitas dan profesionalisme. Penelitian ini memberikan kontribusi orisinal dengan secara sistematis mengintegrasikan pendekatan BSC dengan nilai-nilai Islam dan dapat menjadi model untuk mengevaluasi kinerja sumber daya manusia di lembaga pendidikan Islam lainnya.